Bioelectric Potential of Phaleria macrocarpa (Mahkota Dewa) Fruit: Voltage Measurement and Application as an Alternative Power Source - Rahmaddiansyah, Refa; Aulia Putri Nazhira; Afif Dafakusumah; Fettriwanti; Sukarsi Rusti (Majalah Ilmiah METHODA, 2025)
The use of electrical energy from year to year is increasing, but the source of electrical energy has limitations. This electrical energy crisis must be addressed immediately, one of which is using environmentally friendly and renewable fuels. One of the environmentally friendly sources of electricity is the fruit of the mahkota dewa (Phaleria macrocarpa). The purpose of writing this paper is to investigate the benefits of the crown of the gods as an alternative source of electrical energy. The subject of this research is the crown of the god fruit with the criteria that the fruit is ripe which is marked with a red color which will be used as an alternative source of electrical energy to replace batteries. In addition to its medicinal properties, the results of this study indicate that the crown of the god fruit contains alkaloid compounds (bases) that can generate electricity. The electric voltage generated from the four pieces of the crown of the god can reach a voltage of 1.8 V. Meanwhile, the current generated from one crown of the god is very small and only produces a voltage of 0.9 V. The use of the crown of the gods as a source of electrical energy has a number of advantages in addition to some of the disadvantages it has. Based on the results of research on the power source from the crown of the god, it can be concluded that the hypothesis that there are benefits of the crown of the god as an alternative source of electrical energy is acceptable.